IMPLEMENTATION OF ACADEMIC CULTURE FOR ELEMENTARY SCHOOL STUDENTS' SOCIAL SKILLS - Ardiyansyah Yuliniar Firdaus (Renjana Pendidikan Dasar, 2022)
This study aims to describe the implementation of academic culture for elementary school students' social skills. This type of research uses a descriptive-qualitative approach. The sampling technique used purposive sampling. The informants in this study were teachers and students of SDN Sen Asen 1. Data collection techniques used include observation and documentation. Data analysis using data reduction techniques, data presentation, and drawing conclusions. The results showed that the implementation of academic culture for students 'social skills at SDN Sen Asen 1 was through appreciating friends' achievements, caring about friends when they needed help, and giving and apologizing. Student learning in the classroom through academic culture has an impact on forming students' social habits to be skilled in dealing with their surrounding environment